2010
DOI: 10.1111/j.1365-2826.2010.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Social Stress in the Rat Programmes Neuroendocrine and Behavioural Responses to Stress in the Adult Offspring: Sex‐Specific Effects

Abstract: Stress exposure during pregnancy can 'programme' adult behaviour and hypothalamic-pituitary-adrenal (HPA) axis stress responsiveness. In the present study, we utilised an ethologically relevant social stressor to model the type of stress that pregnant women may experience. We investigated the effects of social defeat by a resident lactating rat over 5 days during the last week of pregnancy on the pregnant intruder rat HPA axis, and on HPA responsivity to stress and anxiety-related behaviour in the adult offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
248
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(270 citation statements)
references
References 101 publications
17
248
3
2
Order By: Relevance
“…A frequent finding reported in mammals is that gestational stress decreases fetal growth rate (Brunton and Russell, 2010; MMN (B). Notice the enlarged cell nuclei (asterisks and outlines) and hypertrophied cytoplasm in MMN hatchlings.…”
Section: Discussionmentioning
confidence: 99%
“…A frequent finding reported in mammals is that gestational stress decreases fetal growth rate (Brunton and Russell, 2010; MMN (B). Notice the enlarged cell nuclei (asterisks and outlines) and hypertrophied cytoplasm in MMN hatchlings.…”
Section: Discussionmentioning
confidence: 99%
“…Our perspective may also provide insights into determining the origin of sex‐specific sensitivity to maternal or developmental stress (Box 3; Bale & Epperson, 2015; Brunton & Russell, 2010; Love et al., 2005). In species where there is disparity in the proximate or ultimate costs of raising a given sex, our framework predicts that the more expensive sex would have a lower threshold to respond to maternal stress given that the costs of errors would be higher compared to the less expensive sex (Love & Williams, 2008; Love et al., 2005).…”
Section: Predicting the Relative Strength Of Vertebrate Maternal‐strementioning
confidence: 99%
“…In nonhuman primates, chronic maternal stress leads to deficits in attention, object permanence, and motor function in offspring, in particular when the stress was experienced early in gestation (Schneider and Coe, 1993;Schneider, 1992;Schneider et al, 1999). In rodent models, prenatal stress induces hypothalamic-pituitary-adrenal (HPA) stress axis dysregulation, heightened behavioral stress reactivity, depression-like behaviors, and cognitive deficits (Bock et al, 2015;Brunton and Russell, 2010;Cottrell and Seckl, 2009;Darnaudéry and Maccari, 2008;Kapoor and Matthews, 2005;Kapoor et al, 2009;Lemaire et al, 2000;Bale, 2007, 2008;Weinstock, 2008). Similar to human studies, the gestational timing of the stress and fetal sex are key determinants in offspring outcome, where studies in both mice and guinea pigs found that prenatal stress produced HPA axis dysregulation and cognitive effects only in male offspring exposed during early or mid-gestation Matthews, 2005, 2008;Kapoor et al, 2009;Bale, 2007, 2008).…”
Section: Prenatal Stress and Neuropsychiatric Vulnerabilitymentioning
confidence: 99%